Mengatasi Permasalahan Residen Dalam Proses Pemulihan Yayasan Mitra Masyarakat Sehat - Berlianti; Thalia Angelina (Yayasan Literasi Sains Indonesia, 2022)
Circulation of drugs is currently very widespread in all circles, both the old and the young, which causes damage to the morale of a person and the nation. Narkoba stands for narcotics, psychotropics, and other illegal drugs. The Ministry of Health of the Republic of Indonesia then introduced another term, namely, NAPZA which stands for narcotics, psychotropics, and addictive substances. Narcotics/Narcotics Crime is a crime that has entered the Disaster phase in Indonesia. The purpose of this study is to find out how evaluations can be carried out in handling drug addicts at the Mitra Sehat Community Foundation. Psychological evaluation is a way to assess and learn about the soul, both about various symptoms, processes and backgrounds. The Social Work Method is a work procedure that must be used in helping and dealing with victims of drug abuse. This practicum aims to find out and examine the problems experienced by addicts so that they can fall into drugs. This type of research uses the Casework method by Zastrow, which is divided into 4 stages, namely; Research Stage, Assessment Stage, Intervention Stage, and Termination Stage. The theory that underlies social casework is basically derived from the theory that underlies social work, as well as various other theories about humans and humanity, namely the dynamic psychology of personality development, personality structure and functions. Every addict has a lot of problems and of course different. Therefore, students take one of the residents to be a client in overcoming the problems faced by the client. Students also make several activities that later can help residents in the problem solving process, such as Master Chef Cooking Competitions, Building an Outdoor Reading Garden, Playing Games, and Morning Gymnastics.